2010
DOI: 10.1104/pp.110.166546
|View full text |Cite
|
Sign up to set email alerts
|

Plastids Contain a Second Sec Translocase System with Essential Functions    

Abstract: Proteins that are synthesized on cytoplasmic ribosomes but function within plastids must be imported and then targeted to one of six plastid locations. Although multiple systems that target proteins to the thylakoid membranes or thylakoid lumen have been identified, a system that can direct the integration of inner envelope membrane proteins from the stroma has not been previously described. Genetics and localization studies were used to show that plastids contain two different Sec systems with distinct functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 75 publications
(91 reference statements)
1
69
0
Order By: Relevance
“…This appears to be due to a breakdown of RNAi, as SCY1 null mutants are stably and uniformly chlorotic (Martin et al, 2009;Skalitzky et al, 2011). qRT-PCR analysis confirmed that both SCY1 and SCY2 transcripts had returned to wildtype levels in the green true leaves (Martin, 2010).…”
Section: Inducible Down-regulation Of Scy2 In Arabidopsismentioning
confidence: 70%
See 4 more Smart Citations
“…This appears to be due to a breakdown of RNAi, as SCY1 null mutants are stably and uniformly chlorotic (Martin et al, 2009;Skalitzky et al, 2011). qRT-PCR analysis confirmed that both SCY1 and SCY2 transcripts had returned to wildtype levels in the green true leaves (Martin, 2010).…”
Section: Inducible Down-regulation Of Scy2 In Arabidopsismentioning
confidence: 70%
“…For example, sodium azide inhibits the thylakoid localization of the SECA1/ SCY1/SECE1-dependent plastocyanin and the 33-kD oxygen-evolving complex protein OE33 (Yuan et al, 1994) without affecting their import into the stroma. In the SEC2 system, SECA2, a stroma-localized homolog to SECA1 and Escherichia coli SECA (Skalitzky et al, 2011), could share a similar sensitivity to sodium azide.…”
Section: Sensitivity Of Imported Proteins To Sodium Azide and Ionophoresmentioning
confidence: 99%
See 3 more Smart Citations